Eucalyptus forestry in Brazilian Pampa biome: between developmental illusion and sustainable inefficacy - Rocha, Jefferson Marçal da; Rocha, Nájila Souza da; Käfer, Pâmela Suélen; Cruz, Rafael Cabral (Ciência e Natura, 2020)
The objective of this article is to analyze how the strategy for the implementation of eucalyptus monoculture in the Brazilian pampa Biome had repercussions on economic, social and environmental aspects. It makes a historical rescue of the formation of the economic development of the region, noting that the forestry project for the region has not escaped the expectations of other strategies imposed on the region in the past, the concentration of wealth of the agrarian elite has never been threatened. Extensive livestock farming, until the beginning of the 20th century, grain monoculture, after World War II, and from the 2000s, forestry, have always been linked to a single logic: the accumulation of capital in the hands of the bourgeoisie. The most aggravating factor in eucalyptus production is the mischaracterization of the Pampa biome, which the richness of this ecosystem, even though it requires better studies, is not taken into account in the policy of forestry expansion. For a legitimate development process is necessary to find endogenous mechanisms to promote development compatible with the improvement of the poorest population and the maintenance of the wealth of the Pampa biome. Factors disregarded in the developmental alternatives proposed for the region to date.